From 0 to 1 : Hive for processing big data (Packt Publishing, 2017)
"This course is an end-to-end, practical guide to using Hive for Big Data processing ... Hive helps you leverage the power of Distributed computing and Hadoop for Analytical processing. Its interface is like an old friend: the very SQL like HiveQL. This course will fill in all the gaps between SQL and what you need to use Hive. End-to-End: The course is an end-to-end guide for using Hive: whether you are analyst who wants to process data or an Engineer who needs to build custom functionality or optimize performance - everything you'll need is right here."--Resource description page